Study on Lecturer Characteristics to Support the Effectiveness gf Entrepreneurship Education at University - Badrud Tamam; Riema Afriani Kusumadewi; Putri Anggraeni (Universitas Ahmad Dahlan, 2023)
The research was motivated by the understanding that entrepreneurship education can improve a nation’s competitiveness, overcome the unemployment explosion, create job opportunities, and promote the nation's economy. The focus of the research problem is how the characteristics of the lecture support the effectiveness of entrepreneurship education at Ciputra University (UC) in producing world-class entrepreneurs. This study aims to gain an overview of lecturer characteristics to help the point of entrepreneurship education at UC. The approach used in this study is the qualitative approach. The qualitative research method used is a case study; the data collection process is done through unstructured observation, in-depth interviews, and documentation study. The determination of the sample of respondents is purposive and snowball. The respondents are the leaders of foundations, institutions/Ltd., faculty, courses, students, and alums. Research steps include: developing categories and instruments, collecting field data, processing data, describing, discussing, concluding, verifying the validity, and preparing research reports. From the research, the researcher concluded: that there are common characteristics for the lecturers who support entrepreneurship education; The recommendations proposed are by adopting a hypothetical model of practical lecture for entrepreneurship education offered in this dissertation which is expected to be an alternative to the development of entrepreneurship education in universities.